The social moderation model: Meta-ethnographic synthesis of local realities in watershed rehabilitation sustainability - Muhammad Al-Kadafi Ilham (Sustainable Urban Development and Environmental Impact Journal, 2026)
Background: Watershed rehabilitation in South Sumatra is a national priority program to address ecological degradation, yet its implementation on the ground has shown highly variable results. This study aims to analyze the determinants that differentiate the success and failure of watershed rehabilitation programs, focusing on the interaction between external interventions and local socio-ecological realities. Methods: Using a Meta-Synthesis (Meta-Ethnography) methodology on qualitative secondary data from studies published between 2020 and 2025, this study translates fragmented findings to build a more comprehensive understanding. Findings: Key findings suggest that the key to success lies not in the technical aspects of planting, but rather in its socio-economic foundations. Failures are generally caused by top-down , project-centric approaches from external stakeholders, which create negative spillover effects, such as rigid targets and tenure conflicts. On the contrary, the success of the program is determined by the existence of a moderation process, where three vital local contexts are tenure security and a sense of ownership, program integration with the subsistence economy through agroforestry, and the involvement of local institutions that are trusted to actively mitigate these negative impacts. Conclusion: This study concludes that the sustainability of watershed rehabilitation requires a paradigm shift from procedural involvement to substantive participation that integrates local knowledge and realities as the main foundation of the program. Novelty/Originality of this article: The novelty of this research lies in its Meta-Ethnographic synthesis of fragmented studies from 2020–2025, proposing a 'Social Moderation Model' that identifies local tenure security and subsistence integration as the definitive core of watershed sustainability, rather than mere technical or procedural participation.